Ten years of experience with herpes zoster vaccine in primary care- how attitudes and practices have changed and what it may mean for a new zoster vaccine. Issue 37 (3rd September 2019) - Guo, Angela; Lindley, Megan C.; Hurley, Laura P.; Allen, Jessica A.; Allison, Mandy A.; O'Leary, Sean T.; Crane, Lori A.; Brtnikova, Michaela; Beaty, Brenda L.; Kempe, Allison; Dooling, Kathleen L.
Abstract: Zoster vaccine live (ZVL [Zostavax]) has been recommended for the prevention of herpes zoster (HZ) among immunocompetent adults ≥60 years in the United States since 2008. To examine changes in healthcare providers' perceptions and practices related to HZ disease and vaccination, we administered surveys to national networks of primary care physicians in 2005, 2008, and 2016. Ten years after ZVL was first licensed, physicians were more likely to respond that they perceived HZ as a serious disease and more strongly recommended ZVL, and were less likely to report less likely to report several major barriers to HZ vaccination such as patient cost, vaccine effectiveness and competing medical concerns. Overall, physician attitudes appear to be more favorable towards zoster vaccination after a decade of availability of a HZ vaccine. The new recombinant zoster vaccine (RZV [Shingrix]) may benefit from physician's increased perception of the importance of HZ and HZ vaccination.